Síntese, caracterização e estudo da atividade citotóxica de complexos de rutênio (II) contendo DPPM e ânions de ácidos quinolina carboxílicos - Silva, Edinaldo Nascimento da (2015)
In this work were synthesized and characterized four new complexes of Ru(II) from the cis- [RuCl2(dppm)2] precursor, dppm =1,1-bis(diphenylphosphino)methane, with the quinoline carboxylate ligands obtained from the acids: quinaldic, quinolinic, kynurenic and xanthurenic. The obtained complexes have the general formula cis-[Ru(OO)( dppm)2]PF6and were characterized by IR, UV-vis and 31P{1H} NMR spectroscopies, elemental analysis of carbon, hydrogen and nitrogen (CHN) and conductivity measurements. From the 31P{1H} NMR spectra was possible to confirm the ligand coordinationto the Ru(II) in the bidentate fashion due to the observation of two triplets signals. In the IR spectra of the complexes there are vibrational modes corresponding to C=N and COO groups characteristic of the quinoline carboxylate ligands. The elemental analysis (CHN) results were consistent with the proposed formulas indicating their purity. The complexes containing the anions of quinaldic acid and kynurenic acid, as well as the cis-[RuCl2(dppm)2] precursor and the reference metallodrug cisplatin were evaluated in the tumor cell lines HepG2 (human hepatocellular carcinoma, liver), MCF-7 (human breast adenocarcinoma) and MO59J (glioblastoma human-brain) and one normal cell line, theGM07492A (normal human lung fibroblasts). The studied complexes have shown promising results in the studied cell lines. The cis-[Ru(quin)(dppm)2]PF6 showed the best results of cytotoxicity in the three tumor cell lines HepG2, MCF-7 and MO59J when compared to the precursor and cisplatin. The activity increased more than 10 times against the cell lines HepG2 and MCF-7 and about 2 times to MO59J when compared with the precursor. When compared with cisplatin the activity decreased approximately 2 times against the cell lines MCF-7 and MO59J and increased 1.6 times against HepG2. The cis- [Ru(quinu)(dppm)2]PF6 complex displayed a MIC of 18 μM against Mycobacterium tuberculosis, this value was only slightly better than that found for the precursor complex.